2006
DOI: 10.1111/j.1460-9592.2006.02096.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of bispectral index during recovery from general anesthesia with 2% propofol and remifentanil in children

Abstract: In preschool children, BIS moderately correlated with the predicted plasma concentration of propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
0
16
1
1
Order By: Relevance
“…This is in contrast to a previous study with children after the surgical repair of congenital heart defects where even a small decrease in cardiac output resulted in a significant decline in cerebral oxygenation [5]. The reason for the increase in cerebral tissue oxygenation might be the decrease in oxygen consumption in a completely sedated brain with reduced electrocortical activity [9,14,22].…”
Section: Discussioncontrasting
confidence: 78%
“…This is in contrast to a previous study with children after the surgical repair of congenital heart defects where even a small decrease in cardiac output resulted in a significant decline in cerebral oxygenation [5]. The reason for the increase in cerebral tissue oxygenation might be the decrease in oxygen consumption in a completely sedated brain with reduced electrocortical activity [9,14,22].…”
Section: Discussioncontrasting
confidence: 78%
“…The Ce propofol at LOC in paediatric patients is significantly higher than in adults. Park's research showed a negative correlation between BIS and propofol plasma concentration [26]. Therefore, we can conclude that larger Ce propofol should be given in paediatric patients to get a similar anaesthetic depth and much larger Ce propofol should be given to get the same BIS values in younger individuals comparing to adults.…”
Section: Baseline Of Bis Loc Rocmentioning
confidence: 93%
“…Park et al aimed that their study was to investigate the relationship between BIS index and predicted plasma concentration of propofol delivered by target-controlled infusion during emergency in children. As a result they concluded that when respiration returned, mean BIS was 77.2 ± 5.3 and propofol plasma concentration 1.6 ± 0.3  μ g/kg and when a verbal command was obeyed, BIS was 82.4 ± 5.6 and propofol plasma concentration 1.5 ± 0.3  μ g/kg and BIS moderately correlated with the predicted plasma concentration of propofol [11]. Zhang et al reported that BIS effectively monitors the depth of intravenous anesthesia with remifentanil and propofol [12].…”
Section: Discussionmentioning
confidence: 99%